The Impact of Wrist Flexibility, Eye-Hand Coordination, and Motivation on Long-Service Skills in Badminton - Yasriuddin, Yasriuddin; Muhammadong, Muhammadong; Hasan, Muh Said; Hudain, Muh. Adnan; Dermawan, Dermawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The type of research is Ex Post Facto, using the Descriptive Analysis Path. The population of this study is all Badminton athletes of PB. Pacific Polman Regency in Makassar. The research sample is a total sampling of 20 athletes. The subjects of the study were Badminton Athletes of PB. Pacific Polman Regency. The results of the study (1). There is a direct influence of sig. Wrist flexibility on long-service stroke skills in badminton athletes of PB. Pacific Polman Regency with a value of r = 0.845 with sig. (p) = 0.000 <0.05. (2) There is a direct influence of hand-eye coordination which is sig. on long-service stroke skills in badminton athletes of PB. Pacific Polman Regency with a value of r = 0.786 with sig. (p) = 0.000 <0.05. (3) There is a direct influence of motivation on long-service stroke skills in badminton athletes of PB. Pacific Polman Regency with a value of r = 0.728 with sig. (p) = 0.000 < 0.05. (4) There is an indirect effect of sig. Wrist flexibility and hand-eye coordination together on long-service stroke skills in badminton athletes of PB. Pacific Polman Regency with a value of r = 0.894 with sig. (p) = 0.000 < 0.05. (5) There is an indirect effect of sig. Wrist flexibility and motivation on long-service stroke skills in badminton athletes of PB. Pacific Polman Regency with a value of r = 0.646 with sig. (p) = 0.000 < 0.05. (6) There is an indirect effect of sig. Hand-eye coordination and motivation on long-service stroke skills in badminton athletes of PB. Pacific Polman Regency with a value of r = 0.908 with sig. (p) = 0.000 < 0.05.(7) There is a significant indirect effect of wrist flexibility, eye-hand coordination and motivation on long-service skills in badminton for PB. Pacific athletes, Polman Regency, with a value of R = 0.738 with sig. (p) = 0.002 < 0.05.